(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article defines the role and place of affirmative particles in the system of expressing modality. The main attention is paid on the characteristics of the stylistic features of these words in the Ukrainian language. The particle yes is multifunctional and combines different meanings, for example, the meaning of agreement, conclusion and sequence of actions. A significant number of synonymous words of affirmative particles are pointed out.